Aesthetic hybridism and innovations in postmodern animated cinema - Souza, Natacha de (Revista do Colóquio, 2025)
Modernity and postmodernity are marked by rapid social and cultural transformations, resulting in a disconnection between the individual, his/her social group and culture, especially at the end of the 20th century. The study of experimental animated cinema, in relation to these phases, seeks to understand how new conceptualizations of art influence the emergence of computational and digital art, taking into account the experience of artisanal production in the cinematographic context. This research appropriates reflections on the technical image, the relations between the modern and the postmodern, and the impact of technological innovations, such as the advent of the camera, on artistic representation. The postmodern, characterized by the hybridization of styles and aesthetic practices, is not configured as an overcoming of the modern, but as a historical condition that questions the rationality of modernity. This article explores contemporary art criticism and its relations with animated cinema, highlighting the tensions between aesthetics and value judgment.